2012
DOI: 10.3109/14992027.2012.701020
|View full text |Cite
|
Sign up to set email alerts
|

Preferred delay and phase-frequency response of open-canal hearing aids with music at low insertion gain

Abstract: In acoustic conditions sensitive to delay effects, delays of 1.4 or 3.4 ms were either not detected or no less preferable than no delayed aided signal. It is unclear whether different phase-frequency responses may be preferred with different music stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, in developing open ear hearing assistive devices that utilize beamforming, the designers need to be less worried on latency constraints from digital signal processing algorithms, and more concerned with distractions that may arise from perceiving one's own voice, as well as audio-visual mismatch. A distorted perception of one's own voice can happen anywhere between 2 and 50 ms (see [22] for a review). This provides a strict constraint of processing delay and would likely need creative solutions to work around.…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, in developing open ear hearing assistive devices that utilize beamforming, the designers need to be less worried on latency constraints from digital signal processing algorithms, and more concerned with distractions that may arise from perceiving one's own voice, as well as audio-visual mismatch. A distorted perception of one's own voice can happen anywhere between 2 and 50 ms (see [22] for a review). This provides a strict constraint of processing delay and would likely need creative solutions to work around.…”
Section: Plos Onementioning
confidence: 99%
“…Although studies testing delays in the range of 1 to >10 ms in simulation have demonstrated negative effects on sound quality as judged by normal and impaired hearing listeners (Stone & Moore, 1999, 2002, 2003, 2005Stone, Moore, Meisenbacker, & Derleth, 2008), these negative effects were not evident when testing in real hearing instruments worn by hearing impaired listeners (Groth & Sondergard, 2004). One study by Zakis, Fulton, and Steele (2012) examined the effect of throughput delay on the sound quality of music in real hearing instruments. In this study, an attempt was made to create a worst case scenario by using open-canal hearing instruments with the gain set such that the likelihood of comb filtering was maximized.…”
Section: Throughput Delaymentioning
confidence: 99%